(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
Basin-margin paralic deposits are sensitive indicators of relative sea-level changes and typically show complex stratigraphic architectures that only a facies-based sequence-stratigraphic approach, supported by detailed biostratigraphic data, can help unravel, thus providing constraints for the tectono-stratigraphic reconstructions of ancient basins. This paper presents a detailed facies analysis of Pliocene strata exposed in a marginal key-area of the northern Siena-Radicofani Basin (Tuscany, Italy), which is used as a ground for a new sequence-stratigraphic scheme of the studied area. The study reveals a more complex sedimentary history than that inferred from the recent geological maps produced as part of the Regional Cartographic Project (CARG), which are based on lithostratigraphic principles. Specifically, four sequences (S1 to S4, in upward stratigraphic order) have been recognised, each bounded by erosional unconformities and deposited within the Zanclean-early Gelasian time span. Each sequence typically comprises fluvial to open marine facies, with deposits of different sequences that show striking lithological similarities.The architecture and internal variability shown by the studied depositional sequences are typical of low-accommodation basin-margin settings, that shows: i) a poorly-developed to missing record of the falling-stage systems tract; ii) a lowstand system tract predominantly made of fluvio-deltaic deposits; iii) a highstand system tract with substantial thickness variation between different sequences due to erosional processes associated with the overlying unconformity; iv) a highly variable transgressive system tract, ranging from elementary to parasequential organization.